-8y+6(y-4)=-18

Simple and best practice solution for -8y+6(y-4)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8y+6(y-4)=-18 equation:


Simplifying
-8y + 6(y + -4) = -18

Reorder the terms:
-8y + 6(-4 + y) = -18
-8y + (-4 * 6 + y * 6) = -18
-8y + (-24 + 6y) = -18

Reorder the terms:
-24 + -8y + 6y = -18

Combine like terms: -8y + 6y = -2y
-24 + -2y = -18

Solving
-24 + -2y = -18

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + -2y = -18 + 24

Combine like terms: -24 + 24 = 0
0 + -2y = -18 + 24
-2y = -18 + 24

Combine like terms: -18 + 24 = 6
-2y = 6

Divide each side by '-2'.
y = -3

Simplifying
y = -3

See similar equations:

| 30x+60y=100 | | 2w-1=-6w+15 | | x+1=19+2x-4+7x+11 | | 3(4n+5)+8n= | | 0=q^2-4q-20 | | -2=5u-7 | | 4(2b+5)=52 | | 1/6x72 | | 2x+80= | | 5x-2y+5x-2y=20 | | n-14+8n= | | -19(13-17x)= | | 8x+12+9x= | | 5m(2n-7)= | | (2x+20)+(6x+40)=180 | | -7(a+7)=-5(4a+6)-6a | | 12+3(4x-6y)-8y= | | 0.50x+0.6=0.3x-1.5 | | 5x^3+14x^2+8x=0 | | (x-(4+3i))(x-(4-3i))=0 | | x^2=-4x+400 | | 3=m/6 | | 3x^4-1=0 | | h=-16t^224*t-3 | | a+2.75+9.35+(2a+2.75+9.35)*0.0715=261.76 | | 2u-4u=-13+11 | | 6(2y+5)-2y+10= | | a+3+9.35+(2a+3+9.35)*0.0715=261.76 | | 3(x-4)=2-2(6-x) | | u^2-10u-9=0 | | -2(m-4)=7m+4(2+7m) | | a+3.25+9.35+(2a+3.25+9.35)*0.0715=261.76 |

Equations solver categories